Supporting data for “A Systematic Study of the In Vitro Pharmacokinetics and Estimated Human In Vivo Clearance of Indole and Indazole-3-Carboxamide Synthetic Cannabinoid Receptor Agonists Detected on the Illicit Drug Market” - Brandon, Andrew; McKenzie, Craig; Antonides, Lysbeth; Read, Kevin (University of Dundee, 2021)
This dataset comprises supporting information for the peer-reviewed manuscript: A Systematic Study of the In Vitro Pharmacokinetics and Estimated Human In Vivo Clearance of Indole and Indazole-3-Carboxamide Synthetic Cannabinoid Receptor Agonists Detected on the Illicit Drug Market published in the journal ‘Molecules’.